Highly Stable, New, Organic‐Inorganic Perovskite (CH3NH3)2PdBr4: Synthesis, Structure, and Physical Properties. Issue 19 (15th March 2018) - Liu, Xixia; Huang, Tang Jiao; Zhang, Liuyang; Tang, Baoshan; Zhang, Nengduo; Shi, Diwen; Gong, Hao
Abstract: Lead halide perovskites have attracted striking attention recently, due to their appealing properties. However, toxicity and stability are two main factors restricting their application. In this work, a less toxic and highly stable Pd‐based hybrid perovskite was experimentally synthesized, after exploring different experimental conditions. This new hybrid organic‐inorganic perovskite (CH3 NH3 )2 PdBr4 was found to be an orthorhombic crystal ( Cmce, Z =4) with lattice parameters a =8.00, b =7.99, c =18.89 Å. The Cmce symmetry and lattice parameters were confirmed using Pawley refinement and the atoms positions were confirmed based on DFT calculation. This perovskite compound was determined to be a p ‐type semiconductor, with a resistivity of 102.9 kΩ cm, a carrier concentration of 3.4 ×10 12 cm −3, and a mobility of 23.4 cm 2 (V s) −1 . Interestingly, XRD and UV/Vis measurements indicated that the phase of this new perovskite was maintained with an optical gap of 1.91 eV after leaving in air with a high humidity of 60 % for 4 days, and unchanged for months in N2 atmosphere; much more stable than most existing organic‐inorganic perovskites. The synthesis and various characterizations of this work further the understanding of this (CH3 NH3 )2 PdBr4 organic‐inorganic hybrid perovskite material. Abstract : Hybrid theory : A new layered organic‐inorganic hybrid perovskite (CH3 NH3 )2 PdBr4 was obtained after trying different experimental conditions. The structure of (CH3 NH3 )2 PdBr4 was determined and optimized. The basic physical properties are measured, showing p ‐type semiconductor characteristics with a 1.91 eV band gap. Impressively, (CH3 NH3 )2 PdBr4 can stabilize its phase and properties for over four days after exposure to air with more than 60 % humidity.